INTERPERSONAL COMMUNICATION MANAGEMENT OF TOURISM AWARENESS GROUP (POKDARWIS) IN KUBU GADANG TOURISM VILLAGE - Musa Hasintongan Jose Pardede; Ernita Arif; Elva Ronaning Roem; Annisa Citra Triyandra (Jurusan Ilmu Komunikasi Universitas Andalas, 2023)
Tourism villages are one of the government's ways to overcome poverty in remote areas in Indonesia. Tourism villages are also able to develop the potential that exists in the area. The Kubu Gadang Tourism Village tourism awareness group also participated in the tourism village concept. The tourism awareness group feels compelled to develop Kubu Gadang Village. This study aims to determine the communication management of tourism awareness groups in developing the Kubu Gadang Tourism Village in Padang Panjang City. The theory used in this study is Michael Kaye's communication management theory, and the method used is qualitative. Data collection techniques using indepth interviews and direct observation. The results showed that the management of interpersonal communication at the Pokdarwis of the Kubu Gadang Tourism Village was well implemented, as seen from the form of support given to the Kubu Gadang Tourism Village.